2007
DOI: 10.1136/jech.2006.052670
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities as a predictor of disability retirement

Abstract: Information on childhood conditions may increase our understanding of the determinants of early retirement, especially due to mental disorders. Childhood adversities should be taken into account when considering determinants of disability retirement and identifying groups at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
103
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 22 publications
(19 reference statements)
8
103
1
6
Order By: Relevance
“…Cognitive and affective impairments may be particularly salient as these may represent the mechanisms by which childhood adversity may directly impact capacity for labour force participation among older adults. Harkonmäki et al (2007) provided some evidence to support this direct pathway between childhood adversity and labour force participation as they found an association between retrospective reporting of a greater number of childhood adversities in a sample of non-retired 40-54 year olds in Finland and an increased risk of permanent sickness in adulthood five years later which was sustained after adjusting for mental health, physical health, and socioeconomic status in adulthood. In addition, Joensuu et al (2015) identified a cluster of young adults on permanent sickness due to mental illness who were characterised by experiences of adversity during childhood which provides further evidence of a direct pathway between adversity and permanent sickness due to mental illness, in adulthood.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Cognitive and affective impairments may be particularly salient as these may represent the mechanisms by which childhood adversity may directly impact capacity for labour force participation among older adults. Harkonmäki et al (2007) provided some evidence to support this direct pathway between childhood adversity and labour force participation as they found an association between retrospective reporting of a greater number of childhood adversities in a sample of non-retired 40-54 year olds in Finland and an increased risk of permanent sickness in adulthood five years later which was sustained after adjusting for mental health, physical health, and socioeconomic status in adulthood. In addition, Joensuu et al (2015) identified a cluster of young adults on permanent sickness due to mental illness who were characterised by experiences of adversity during childhood which provides further evidence of a direct pathway between adversity and permanent sickness due to mental illness, in adulthood.…”
mentioning
confidence: 89%
“…Moreover, previous studies have often focused exclusively on a cumulative adversity measure (e.g. Harkonmäki et al 2007) which limits understanding as to whether particular adversities are driving effects. In addition, the comparability of Finnish or other national cohorts to a UK population is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have just compared obese vs nonobese subjects, 22 lumping the underweight, normal weight and overweight together. As the BMI-disability pension association exhibits quite different magnitudes of risk in the different BMI strata defined by the WHO, distortions are easily introduced.…”
Section: Bmi Status and Disability Pension M Neovius Et Almentioning
confidence: 99%
“…2,11,15,22 Such an approach is associated with at least two limitations; first, persons who receive a disability pension or die before that age are excluded. Second, the risk of reverse causation increases, as the prevalence of pre-existing illness affecting BMI, for example, cancer, is higher.…”
Section: Bmi Status and Disability Pension M Neovius Et Almentioning
confidence: 99%